Effect of bleaching gel volume on color change and postoperative sensitivity: a randomized clinical study - Esteves, Lara Maria Bueno [UNESP]; Santos, Paulo Henrique dos [UNESP]; Fagundes, Ticiane Cestari [UNESP]; de Oliveira Gallinari, Marjorie; de Mello Antonaccio, Giulia Bessa [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Briso, André Luiz Fraga [UNESP] (Springer Nature, 2022)
Objectives: Although bleaching therapy is considered a dose-dependent treatment, the effect of the volume of product used is yet to be studied. This study thus aimed to evaluate the influence of bleaching gel volume on chromatic alteration and postoperative sensitivity. Methodology: Thirty patients were selected and allocated into three groups; the lower canines were analyzed according to the volume of gel used: GI-0.025 mL, GII-0.05 mL, and GIII-0.10 mL. Chromatic alteration analysis was performed using a portable digital spectrophotometer by calculating the ΔE, ΔE00, ΔL*, Δa*, and Δb* values and the whiteness index (WID). Spontaneous sensitivity was assessed using a questionnaire, and sensitivity was stimulated by thermo-sensory analysis. Analyses were conducted in five stages: baseline, after 1st, 2nd, and 3rd bleaching sessions, and 14 days after the end. Data were analyzed using the two-way ANOVA test with repeated measures and Tukey’s post hoc test (p < 0.05). Results: It was observed that ΔE, ΔE00, and ΔL* were similar between groups at the end of the bleaching therapy; and the values of Δa*, Δb*, and WID were higher in the GIII group. For sensitivity, it was found that the GI was the one with the lowest values; o GII intermediate values; while the GIII group presents the highest values of spontaneous and stimulated sensitivity. Conclusion: Gel volume influenced the response to bleaching and significantly influenced the spontaneous sensitivity and cold stimulus. Clinical relevance. The amount of bleaching gel used during therapy is key to both the response to color change and postoperative sensitivity.
Keywords: Clinical protocols; Color analysis; Hydrogen peroxide; Tooth bleaching; Tooth sensitivity; Whitening